Management Strategy Evaluation: Allowing the Light on the Hill to Illuminate More Than One Species - Kaplan, Isaac C.; Gaichas, Sarah K.; Stawitz, Christine C.; Lynch, Patrick D.; Marshall, Kristin N.; Deroba, Jonathan J.; Masi, Michelle; Brodziak, Jon K. T.; Aydin, Kerim Y.; Holsman, Kirstin; Townsend, Howard; Tommasi, Desiree; et al. (Frontiers in Marine Science, 2021)
Management strategy evaluation (MSE) is a simulation approach that serves as a “light on the hill” (Smith, 1994) to test options for marine management, monitoring, and assessment against simulated ecosystem and fishery dynamics, including uncertainty in ecological and fishery processes and observations. MSE has become a key method to evaluate trade-offs between management objectives and to communicate with decision makers. Here we describe how and why MSE is continuing to grow from a single species approach to one relevant to multi-species and ecosystem-based management. In particular, different ecosystem modeling approaches can fit within the MSE process to meet particular natural resource management needs. We present four case studies that illustrate how MSE is expanding to include ecosystem considerations and ecosystem models as ‘operating models’ (i.e. virtual test worlds), and to simulate monitoring, assessment, harvest control rules, and performance metrics. We highlight U.S.A. case studies related to fisheries regulations and climate, which support NOAA’s policy goals related to the Ecosystem Based Fishery Roadmap and Climate Science Strategy but vary in the complexity of population, ecosystem, and assessment representation. We emphasize methods, tool development, and lessons learned that are relevant beyond the U.S.A., and the benefits relative to single-species MSE approaches.